The Impact of Basketball Extracurricular Activities on Student Learning Motivation: A Quantitative Study - Arsad, M Rafli Ode; Syam Tuasikal, Abdul Rachman; Siantoro, Gigih (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2025)
This study aims to examine the impact of basketball extracurricular activities on junior high school students’ learning motivation. Employing a pretest-posttest control group design, the research involved 70 eighth-grade students divided into experimental and control groups. Data were collected using a learning motivation questionnaire adapted from the Self-Determination Scale with adequate reliability. The findings revealed a significant improvement in learning motivation among the experimental group compared to the control group. The mean score increased from 28.40 to 30.80, with the Wilcoxon test showing Z = -3.336 and p = 0.001 (<0.05). These results confirm that participation in basketball extracurricular activities can enhance students’ intrinsic motivation, which positively influences their learning engagement and outcomes. Nevertheless, a small proportion of students experienced decreased motivation, possibly due to fatigue, unmet expectations, or scheduling conflicts. This study recommends that schools design more adaptive and balanced extracurricular programs to ensure that the benefits of sports activities are maximized for all students